The Strategic Management Process for Innovation Activities of OMAN Telecommunication Company (OMANTEL) - Al Abri, Sultan (Advances in Social Sciences Research Journal, 2021)
This research will investigate on the strategic management process of the entrepreneurship and innovation activities of Oman Telecommunication Company (OMANTEL). It will assess the chosen organization’s (Omantel) characteristic that is facilitating innovative process, implement activities that establishes an innovative environment within the structure of an organisation and analyse the strategic approach of the company’s innovation management. Moreso, this will also outline a discussion on the dynamics and characteristics of Omantel company and how the ICV policy could be improved; and will analyse as well the strategic management process adopted by Omantel company in driving entrepreneurship and innovation. To achieve these objectives, the relevant sources of information to be utilized include online articles, books and relevant entrepreneurship, innovation and SME journals. Finally, recommendations were made to improve the organization’s innovation process; foremost of which is a program that would provide new skills and knowledge to employees to foster creativity and innovation across organization.